1997
DOI: 10.1038/ki.1997.392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetate on energy metabolism and function in the isolated perfused rat heart

Abstract: Impairment of cardiac contractile function is an important component of acetate associated hypotension during hemodialysis treatments. We examined the effect of acetate on cardiac energy metabolism using the isovolumic isolated perfused heart model. In this preparation, acetate (10 M) caused decreases in tissue ATP concentrations (12.3 +/- 0.8 vs. 15.6 +/- 1.0 micromol/g dry at 30 min, P < 0.05) as well as marked impairment of systolic function (dpdt = 863 +/- 135 vs. 1288 +/- 166 mm Hg/second at 30 min, P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Bicarbonate-based hemofiltration replacement fluids have not yet been approved in Germany. Previous studies had suggested that the metabolism of acetate and lactate is impaired in critical illness and this might be able to produce acidosis [3,4]. Furthermore, it has been suggested that lactate and acetate might act as cardiovascular depressants [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bicarbonate-based hemofiltration replacement fluids have not yet been approved in Germany. Previous studies had suggested that the metabolism of acetate and lactate is impaired in critical illness and this might be able to produce acidosis [3,4]. Furthermore, it has been suggested that lactate and acetate might act as cardiovascular depressants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had suggested that the metabolism of acetate and lactate is impaired in critical illness and this might be able to produce acidosis [3,4]. Furthermore, it has been suggested that lactate and acetate might act as cardiovascular depressants [4]. The present trial was designed to assess the impact of different hemofiltration fluids on the acid-base status of patients requiring treatment with CVVH in an intensive care unit.…”
Section: Introductionmentioning
confidence: 99%
“…32 Also, acetate can impair the fatty acid metabolism of muscle cells, reducing adenosine triphosphate and the contractile force of the myocardium, but such deleterious effects seem to occur only at relatively high plasma concentrations. 33 Colloids are able to better expand the circulatory blood volume due to their higher colloid osmotic pressure compared to crystalloids. 34,35 HES and GEL were chosen because of controversies related to immunomodulatory effects 36 and kidney damage.…”
Section: Choice Of Fluid Replacement Therapymentioning
confidence: 99%
“…Among them, acetate leads to a decrease in ATP production and tissue ATP concentrations that ultimately results in impaired cardiac contractile function [18]. As this occurs at relatively low concentrations of acetate (0.1-1 mmol/l), this finding is relevant to acetate-containing dialysate used for substitution fluid in on-line hemodiafiltration.…”
Section: Acetate-free Dialysate For On-line Hemodiafiltrationmentioning
confidence: 89%